Nilai-Nilai Pendidikan Humanis Perspektif Muhammad Nur Abdul Hafidz Suwaid Dalam Buku Prophetic Parenting - akhbar, toyib; Hakim, Rahmad (Mu'allim, 2025)
This study aims to analyze the humanist educational values from the perspective of Muhammad Nur Abdul Hafidz Suwaid in his work Prophetic Parenting. This book offers an educational approach based on prophetic values derived from the teachings of the Prophet Muhammad SAW, with an emphasis on aspects of compassion, appreciation of children's potential, effective communication, and the development of noble character and morals. The humanist approach in education proposed by Suwaid emphasizes the importance of understanding children's psychology, creating positive emotional relationships between children and parents, and establishing a learning environment filled with love and trust. This study uses a qualitative approach with a type of literature research. The data collection technique is document elicitation. Meanwhile, the data analysis technique uses content analysis. The results of the study show that the humanist educational values from the perspective of Muhammad Nur Abdul Hafidz Suwaid in his work Prophetic Parenting are as follows: empathy, justice, respect for children's individuality, and the integration of religious values with daily life, which are essential foundations in the practice of humanist education. These values are relevant for application in the context of family education and formal educational institutions to respond to current educational challenges.